Vasile Alecsandri’s Peasants. The Peasant’s Image in Vasile Alecsandri’s Work - BĂRBULESCU, Constantin (Studia Universitatis Babeș-Bolyai Historia, 2016)
Vasile Alecsandri’s Peasants. The Peasant’s Image in Vasile Alecsan-dri’s Work. I am trying to present in this paper the image of the Romanian peasant as it appears in the work of a representative writer of the 19th century: Vasile Alec-sandri. Or, happily for us, the peasant is an important character in Alecsandri’s writings. I excluded the pleys from this research. In other words I have studied correspondence, poetry and prose. The multishape image of the peasant can be structured in few independent topics. Thus, I have identified the topics of the oppressed peasant, the hero peasant, the picturesque peasant, the real peasant (in correspondence) and finally the good peasant. In Vasile Alecsandri’s work the dominant dimension of the peasant’s image is a positive one. We are here in the paradigm of the identitary peasant, that as we know now is not unique in the 19th century. Rezumat: ţăranii lui Vasile Alecsandri. Imaginea ţăranului în opera lui Vasile A-lecsandri. În lucrarea de faţă am încercat să surprindem imaginea ţăranului român aşa cum apare ea în opera unui scriitor reprezentativ din secolul al XIX-lea: Vasile Alecsandri. Or, din fericire pentru noi, ţăranul este un personaj important în toate scrierile lui Vasile Alecsandri. Am exclus din această cercetare dramaturgia. Cu alte cuvinte am lucrat pe corespondenţă, poezie şi proză. Imaginea multiformă a ţăranului poate fi structurată în câteva teme de sine stătătoare. Am identificat astfel tema ţăranului chinuit, a ţăranului erou, a celui pitoresc, a celui real (din corespondenţă) şi, în final, ţăranul cel bun. În opera lui Vasile Alecsandri dimen-siunea dominantă a imaginii ţăranului este una pozitivă. În marea majoritate a situaţiilor ţăranul este un personaj pozitiv. Suntem aici în paradigma ţăranului identitar, care, acum ştim, nu este unică în secolul al XIX-lea. Cuvinte-cheie: literatură, secolul al XIX-lea, ţăran, imaginea ţăranului, istorie